A Nano‐Micro Hybrid Structure Composed of Fe7S8 Nanoparticles Embedded in Nitrogen‐Doped Porous Carbon Framework for High‐Performance Lithium/Sodium‐Ion Batteries. (19th June 2018) - Liu, Zhiming; Hu, Fang; Xiang, Juan; Yue, Chuang; Lee, Dongsoo; Song, Taeseup
Abstract: Iron sulfides are attractive anode materials for lithium‐ion batteries (LIBs) and sodium‐ion batteries (SIBs) due to their high theoretical capacities, low cost, and eco‐friendliness. However, their real application is greatly hindered by the rapid capacity fading caused by the large volume changes and sluggish kinetics of iron sulfides during the charge and discharge processes. Combining with carbonaceous materials and tuning the structure at nanoscale are essential to address this issue. Here, a facile hydrothermal method coupled with a carbonization process is developed to synthesize a nano‐micro hybrid porous structure, which is composed of Fe7 S8 nanoparticles embedded in nitrogen‐doped carbon framework (Fe7 S8 @NC‐PS). This hierarchical sphere is constructed by interconnected 2D nanowalls. The as‐prepared Fe7 S8 @NC‐PS electrodes reveal excellent rate capability and cycling stability in LIBs and SIBs. The remarkable electrochemical properties are attributed to the porous nano‐micro hybrid architecture and the high conductivity and structural stability of the nitrogen‐doped carbon framework. Abstract : A nano‐micro hybrid structure composed of Fe7 S8 nanoparticles embedded in nitrogen‐doped porous carbon framework is applied in lithium/sodium‐ion batteries and shows remarkable electrochemical properties, which is attributed to buffering effect of the porous structure and the high conductivity and structural stability of the nitrogen‐doped carbon framework.